Peran Les Privat Mahasiswa KPM Insuri Terhadap Peningkatan Prestasi Belajar di Lingkungan Dukuh Sekuwung Desa Kedungbanteng - Alfi Nur Azizah; Maulida Agustina Hidayatul Wahidah; Samsudin Samsudin (Social Science Academic, 2025)
Private tutoring in the modern education system encourages many parties to evaluate their impact on student learning outcomes and find ways to optimize their implementation. This study aims to analyze the role of private tutoring given by Community Service Lecture (KPM) students from the Sunan Giri Ponorogo Islamic Institute (Insuri) on the improvement of student learning achievement at SDN 4 Kedung Banteng, Ponorogo. The research method used is a qualitative method with a descriptive approach. Data was collected through observation, interviews, and documentation. The findings of the study show that private tutoring of KPM Insuri students contributes positively to the improvement of student learning achievement, especially in mathematics and Indonesian subjects. Factors that contribute to the success of private tutoring include a more personalized approach to learning, more intensive attention from tutors, and the use of innovative learning methods. However, the study also identified challenges such as time constraints and student attendance consistency. The conclusion of this study is that private tutoring for KPM Insuri students is effective in improving students' academic achievement and there needs to be better planning and support from all parties to achieve optimal results.